THE ASSESSMENT OF ECOTOPES’ ENVIRONMENT SATISFACTORINESS AND PREDICTIVE MODELLING OF CONDITIONS FOR COENOPOPULATIONS OF RARITY FOREST FLORA SPECIES (THE CASE OF Tulipa quercetorum Klock. Et Zoz.) - Bondaruk, M. A.; Tselishchev, A. G. (Forestry and Forest Melioration, 2018)
Introduction The integrated procedure of the assessment of ecotopes’ environment satisfactoriness, adaptive potential of the rare forest flora species and predictive modelling of conditions of their coenopopulations were methodologically substantiated and developed on the basis of modern scientific researches. The topicality of the research is caused by the international duties related to biota diversity and natural landscapes conservation, as well as sustainable forest management, accepted by Ukraine to solve at the national level. Materials and methods By means of phytoindication analysis with the superposition of the species ecological amplitudes according to the ecological scales for the Ukrainian species (Ya.P. Didukh, 2011) and plant communities, the comparison of numerical score dynamic for ecotopes’ ecological regimes with the width of appropriate tolerance amplitudes for rare and endangered forest species and the calculation of environment satisfactoriness coefficients (there were analyzed 7 edaphic and 4 microclimatic ecoregimes) the environment satisfactoriness for the ecotopes of maple-linden oakeries in woodland "Great Forest" were assessed and predictive modelling of the conditions for coenopopulations of endemic species Tulipa quercetorum Klock. Et Zoz., included in the Ukrainian Red Book and IUCN list (category - Vulnerable), was made. The criticality level of its coenopopulations, possibilities to enlarge their localities area and distribution within the woodland were investigated. Results. Discussion Vector distribution of environment gradients and, additionally, anthropogenic influence were recognized as the main reasons of the aggregated distribution of the individuals of Tulipa quercetorum populations within the woodland ecotopes. Close to optimal and satisfied (in some localities) ecological regimes allow predicting stable long-term existence of coenopopulations with rather high characteristics of abundance – covering and vitality. The species distribution outside its localities is limited by the humidity (ombroregime) and microclimate continentality and restricted by soil moisture variability. The differentiate nature management regime with the network form of conservation (establishment of microreserves with the areas of 0.25–1 ha in places of Tulipa quercetorum individuals concentration with the annual monitoring of coenopopulations condition, elimination of these plots from recreational forest using and limitation of economic activity) is proposed for Tulipa quercetorum conservation. Conclusions The comparison of numerical score dynamic for ecotopes’ ecological regimes with the width of appropriate tolerance amplitudes for rare and endangered forest species and the calculation of environment satisfactoriness coefficients allows to estimate the possibilities of regress and progress development of their coenopopulations, to optimize their conservation strategy, as well as determine the suitability of phytoindication for ecological investigations, expertises and monitoring.